(untitled) (Web of Teachers: Inderscience Research, 2026)
This article highlights the importance of multimedia tools in developing literacy in primary school students, their impact on the educational process, and ways to implement them effectively. The advantages of multimedia resources and practical experience in their application in educational conditions are also analyzed.